Stress e insegnamento: contributo all'indagine sulle strategie di coping degli insegnanti in Italia - Riccardo Sartori; Cristina Maria Rappagliosi (LED Edizioni Universitarie, 2011)
Stress and Teaching: A Contribution to the Enquiry on the Coping Strategies of Teachers in Italy The paper presents the results of a study carried out with 254 teachers from North, Central and South Italy belonging to primary and secondary schools. In the last decade, the Italian school system has experienced a series of radical changes that have forced teachers to deeply modify their methods and conception of work. This has caused them to continually adapt and readapt, thereby becoming more vulnerable to stress. Nevertheless, some of them seem to be more capable of facing problematic events. This study aimed to analyse which coping strategies teachers adopt when they find themselves dealing with difficult situations or stressful events. To this end, a questionnaire was used, consisting of: 12 items for personal data, 28 items from the «Brief Cope» («Coping orientation to problems experienced» by Carver, Scheier, & Weintrab, 1989), 21 items from the Italian version by Caprara (2001) of Bandura's Teacher Self-efficacy Scale (1977) and 12 items from the Motivation Questionnaire by Galati, Fassio and Viarengo (2006). Results show that the coping strategies adopted by Italian teachers are in relation to gender (males and females use the same strategies with different frequencies), age and service (young and old use different strategies) and the perception of self-efficacy. Self-efficacy is also in relation to teachers' motivation to work.